2017
DOI: 10.9790/3008-1202025358
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies of Some Medicinal Plants Extracts for Antiviral Activity against Rotavirus

Abstract: Every year, Rotavirus infection is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Pre-clinical investigations ( in-vitro and in-vivo ) of garlic extract (GE) and its OSCs have shown antiviral activity against a wide range of viral infections including flu and respiratory infections ( Chavan et al, 2016 ; Chen et al, 2011 ; Choi, 2018 ; Liu et al, 2013 ; Mehmood et al, 2018 ; Mehrbod et al, 2009 ; Mehrbod et al, 2013 ; Mohajer Shojai et al, 2016 ; Rasool et al, 2017 ; Tsai et al, 1985 ; Weber et al, 1992 ), immunosuppression (“ Garlic extract for HIV? ", 1998 ; Kun Silprasit et al, 2011 ; Shoji et al, 1993 ; Tatarintsev et al, 1992 ; Walder et al, 1997 ), genital herpes ( Romeilah et al, 2010 ; Weber et al, 1992 ), neurological infections ( Luo et al, 2001 ; Meléndez-Villanueva et al, 2019 ; Wang et al, 2016 ), gastrointestinal infections ( Al-Ballawi et al, 2017 ; Weber et al, 1992 ), plant infections ( Mohamed, 2010 ; Shyam & Ashish, 2011 ; Wang et al, 2020 ) and others ( Liu et al, 2013 ; Seo et al, 2017 ; Wang et al, 2017 Weber et al, 1992 ) ( Table 3 , Table 4 ). Further, randomized clinical trials on different commercial garlic preparations also showed that garlic plays a significant therapeutic role in various viral infections such as cold and flu, viral-induced hepatitis, viral-associated warts, as well as immune enhancing activity in viral infected patients ( Table 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical investigations ( in-vitro and in-vivo ) of garlic extract (GE) and its OSCs have shown antiviral activity against a wide range of viral infections including flu and respiratory infections ( Chavan et al, 2016 ; Chen et al, 2011 ; Choi, 2018 ; Liu et al, 2013 ; Mehmood et al, 2018 ; Mehrbod et al, 2009 ; Mehrbod et al, 2013 ; Mohajer Shojai et al, 2016 ; Rasool et al, 2017 ; Tsai et al, 1985 ; Weber et al, 1992 ), immunosuppression (“ Garlic extract for HIV? ", 1998 ; Kun Silprasit et al, 2011 ; Shoji et al, 1993 ; Tatarintsev et al, 1992 ; Walder et al, 1997 ), genital herpes ( Romeilah et al, 2010 ; Weber et al, 1992 ), neurological infections ( Luo et al, 2001 ; Meléndez-Villanueva et al, 2019 ; Wang et al, 2016 ), gastrointestinal infections ( Al-Ballawi et al, 2017 ; Weber et al, 1992 ), plant infections ( Mohamed, 2010 ; Shyam & Ashish, 2011 ; Wang et al, 2020 ) and others ( Liu et al, 2013 ; Seo et al, 2017 ; Wang et al, 2017 Weber et al, 1992 ) ( Table 3 , Table 4 ). Further, randomized clinical trials on different commercial garlic preparations also showed that garlic plays a significant therapeutic role in various viral infections such as cold and flu, viral-induced hepatitis, viral-associated warts, as well as immune enhancing activity in viral infected patients ( Table 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…El bulbo ha demostrado actividad antiviral por inhibición de integrinas, previene la fusión viral e invasión por inhibición del receptor celular ACE2, aumenta la inmunidad y los anticuerpos neutralizantes. Es efectivo en el manejo de infecciones por CMV, CXV, VIA, parainfluenza, rhinovirus, rotavirus (Al-Ballawi et al, 2017), VHS, VIH e inclusive SARS-CoV-2 (Phuong Thuy et al, 2020). Además de sus propiedades antimicrobianas e inmunomoduladoras del sistema respiratorio, tiene propiedades para disminuir las infecciones oportunistas en casos de VIH (Mukhtar et al, 2008) y en el manejo de enfermedades crónicas (Alam et al, 2016;Bayan et al, 2014).…”
Section: Principales Plantas Con Actividad Antiviral Disponibles En Guatemalaunclassified
“…De origen asiático cultivadas en Guatemala, se encontró que el rizoma de jengibre (Zingiber officinale Rosoe, Zingiberaceae) inhibe la agregación de células infectadas por el virus usando técnicas in vitro y es activo contra HSV-1 y 2, rotavirus (Al-Ballawi et al, 2017), VIA y VSR (Chang et al, 2013) por inhibición de la internalización viral y el té de limón (Cymbopogon citratus (DC) Stapf y C. nardus (L.) Rendle, Poaceae) activos contra HSV-1, rotavirus y VIH (Chiamenti et al, 2019;Feriotto et al, 2017;Richling, 2009). De origen europeo, la hiedra (Hedera helix L., Araliaceae) importada en Guatemala, es una planta activa contra enterovirus y VIA (Hong et al, 2015;Lutsenko et al, 2010;Song et al, 2014), así como antiinflamatoria y expectorante (Al-Snafi, 2018) y la albahaca (Ocimum basilicum L., Lamiaceae) ampliamente cultivada en el país, presenta actividad contra adenovirus, CXV, VHB y VHS-1 (Amber et al, 2016;Chiang et al, 2005;Romeilah et al, 2010).…”
unclassified
“…The great diversity of plants and the lack of effective therapies and vaccines for ASF have urged a growing need for developing new, effective and safe agents to limit the spread of the disease. There are innumerable potentially useful plant extracts and herbs, and some of them have been shown to have great medicinal value in the prevention or treatment of viral diseases [21]. Scientific databases contain a huge number of articles on the antiviral, antifungal, antibacterial and even anthelmintic effects of medicinal herbs and plant extracts [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%